2020
DOI: 10.1186/s12966-020-01025-3
|View full text |Cite
|
Sign up to set email alerts
|

A whole family-based physical activity promotion intervention: findings from the families reporting every step to health (FRESH) pilot randomised controlled trial

Abstract: Introduction This study assessed the feasibility and acceptability of FRESH (Families Reporting Every Step to Health), a theory-based child-led family physical activity (PA) intervention delivered online. We also assessed the preliminary effectiveness of the intervention on outcomes of interest and whether pre-specified criteria were met to progress to a full-scale definitive trial. Methods In a three-armed randomised pilot trial, 41 families (with a 7–11-year-old index child) were allocated to a: ‘family’ (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(48 citation statements)
references
References 68 publications
4
41
3
Order By: Relevance
“…There is robust evidence of the associated positive outcomes of parental engagement in school-based prevention programs [27][28][29]. This evidence is consistent with Bronfenbrenner's ecological systems theory [30,31], which proposes that interactions with parents around learned topics at school might help address internalizing concerns [4,32].…”
Section: Discussionsupporting
confidence: 57%
“…There is robust evidence of the associated positive outcomes of parental engagement in school-based prevention programs [27][28][29]. This evidence is consistent with Bronfenbrenner's ecological systems theory [30,31], which proposes that interactions with parents around learned topics at school might help address internalizing concerns [4,32].…”
Section: Discussionsupporting
confidence: 57%
“…12,15 Recruitment of families to research projects is particularly challenging. 9,[16][17][18] Elsewhere, we have described specific recruitment challenges we have encountered in previous work, [19][20][21] but there has not been a comprehensive assessment of how to recruit families to family-based health promotion research.…”
mentioning
confidence: 99%
“…Some children commented how ‘inspiring people’ and role models often motivate them to be engaged in PA. Recent research has shown that family-based interventions are rated as more ‘fun’ and result in greater improvements in MVPA [ 153 ] and so strategies to enhance PA could therefore target co-participation via family-wide interventions, which would confer the additional benefits of social support and adult behavioural modelling. Social support from family, friends, teachers, and coaches could also be utilised in strategies to assist children in overcoming the discussed perceived barriers to PA for this population.…”
Section: Discussionmentioning
confidence: 99%